Six Sigma Analysis of Halal Food Packaging Defects: Analisis Six Sigma terhadap Cacat Kemasan Makanan Halal - Nurria Peppi Yuwana; Hana Catur Wahyuni (Indonesian Journal of Innovation Studies, 2025)
General Background: Product quality control is a critical requirement in manufacturing industries to maintain production consistency, reduce defects, and support customer satisfaction. Specific Background: PT. XYZ, a wafer manufacturing company, experienced a packaging defect rate of 1.24% over a 12-month period, exceeding the company’s tolerance limit of 1%, with 7,962 defective packages recorded during production. Knowledge Gap: Previous studies have applied Six Sigma to packaging quality problems; however, limited studies have integrated Six Sigma (DMAIC), Root Cause Analysis (RCA), and a 5W+1H approach using a long-term observation period to identify the root causes of packaging defects in halal food products. Aims: This study aimed to identify the dominant packaging defect, determine its root causes, and formulate improvement recommendations to reduce defects within the company’s tolerance limits. Results: The findings revealed 12 types of packaging defects, with endseal corner tear defects representing the largest proportion at 44% of total defects. The average Defect Per Million Opportunities (DPMO) value was 1,131.46, and the average sigma level was 4.56. Root cause analysis identified five contributing factors: method, machine, man, environment, and material. Novelty: The study integrates Six Sigma DMAIC, RCA, fishbone analysis, and 5W+1H within a 12-month evaluation framework to provide a comprehensive diagnosis of packaging quality issues. Implications: The proposed corrective actions, including machine maintenance, standardized operating procedures, process monitoring, operator training, and material control, can serve as a reference for reducing packaging defects and improving production quality management in halal food manufacturing.Highlights: Endseal corner tear accounted for 44% of total packaging nonconformities. Average process performance reached 1,131.46 DPMO with a sigma level of 4.56. Five primary causal categories were identified: method, machine, man, environment, and material. Keywords: Six Sigma; Root Cause Analysis; Packaging Quality; Halal Food Products; DMAIC